Heavy Metals in Over-the-Counter Pediatric Drugs Locally Produced in Uganda: A Stare at Manganese, Lead, and Cadmium: Heavy metals in OTC pediatric drugs - Olutona, Godwin O; Mulungi, Joel (Iranian Journal of Pharmaceutical Sciences, 2022)
This study evaluated the amounts of lead (Pb), cadmium (Cd), and manganese (Mn) in pediatric over-the-counter medications made in Uganda. Twelve distinct brands from four categories of pediatric medications (antihistamine, cough expectorant, antipyretic and analgesic, and cold and flu medication) were chosen at random from Kampala's drug stores. Before acid digestion, the syrups were washed with concentrated HNO3:HClO4 (5:1), and the metals were measured using FAAS AAnalyst 400. The average values (µg/mL) found were as follows: antihistamine (Cd, 0.89±0.122; Pb, 7.01±10.0); cold and flu (Cd, 0.89±0.073; Pb, 1.69±0.718); cough expectorant (Cd, 0.14±0.0196; Pb, 1.55±1.332); and antipyretics and analgesic (Cd, 0.16±0.774; Pb, 1.76±1.123). Antihistamines and medications for the cold and flu were not detectable in sample codes (A1 and B1), respectively. In every sample examined, manganese levels were below the non-detectable threshold. The different coefficient of variation (CV) values found in this investigation demonstrated that the metals in pediatric medications came from a wide variety of sources. According to total metal content, each brand of pediatric medication contains Antihistamine (56%), Antipyretic and analgesic (15%), Cold and flu (15%), and Cough expectorant (14%). Uganda's pediatric medicine producers should be closely watched by the National Drug Agency.